2016
DOI: 10.18178/ijcea.2016.7.4.588
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Intermediate Compounds of Phenol in Photocatalysis Process

Abstract: Abstract-Determining the degradation mechanism of phenol under illumination of titanium dioxide (TiO 2 ) is main task in this present work. The experiment carried out with 100 ppm of phenol solution and 0.9 g/L TiO 2 under UV-C light. The COD and UV-Vis measurement were applied in the present work to evaluate the efficiency of phenol removal. The results showed that photocatalysis removed effectively phenol from water after 24 hours of UV-C illumination. In the first 16 hours, there was a slight decrease in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…This effect is attributed to the further degradation of phenolic compounds in other products, not detected with the TPC analysis, occurred during the light irradiation period. 55 Previous studies pointed out that photocatalysis exerts a strong oxidation action and so, the initial products can be further oxidized. 20,22,55 On the other hand, considering the experiments 1, 4, 7, 9, 10, where a medium and high concentration of catalyst was tested, an opposite effect of photocatalysis was observed (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This effect is attributed to the further degradation of phenolic compounds in other products, not detected with the TPC analysis, occurred during the light irradiation period. 55 Previous studies pointed out that photocatalysis exerts a strong oxidation action and so, the initial products can be further oxidized. 20,22,55 On the other hand, considering the experiments 1, 4, 7, 9, 10, where a medium and high concentration of catalyst was tested, an opposite effect of photocatalysis was observed (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the results reported in Figure 5b show that 2ZnO/s-PS δ-form aerogel is also able to reduce the TOC after each cycle, always leading to a TOC removal of 86% after 180 min of UV irradiation. The small difference between the final values of phenol degradation and TOC removal was possibly due to the formation, during the degradation processes, of some intermediates, such as hydroquinone, benzoquinone and organic acids, some of which were not readily degradable [21,22,23].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Dang et al reported photocatalytic oxidation of phenol over TiO 2 photocatalyst. They found that aromatic pollutant phenol could be further degraded into other intermediate quinone rings such as ortho‐dihydroquinone, ortho‐benzoquinone, hydroxydydroquinone, and hydroxybenzoquinone by reaction withOH • .…”
Section: Resultsmentioning
confidence: 99%